KEMAMPUAN MENULIS NARASI DIKAITKAN DENGAN SIKAP BAHASA DAN PENGETAHUAN EJAAN BAHASA INDONESIA (EBI) DI KELAS V SD NEGERI SERANG 5 KOTA SERANG: KEMAMPUAN MENULIS NARASI DIKAITKAN DENGAN SIKAP BAHASA DAN PENGETAHUAN EJAAN BAHASA INDONESIA (EBI) DI KELAS V SD NEGERI SERANG 5 KOTA SERANG - Asep - Muhyidin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2017)
Abstract This study aims to determine empirically the relationship of language attitudes and knowledge of Indonesian spelling (EBI) with writing narrative competence in class V SDN Serang 5 Serang City. The study was conducted on the students of class V of the odd semester of the academic year 2016/2017. The research method used in this research is survey method with correlational study approach. The population of this study is all students of class V SDN Serang 5 Serang City which amounted to 44 students. The data collection in this study is to use test instruments and questionnaires. Based on the results of research and discussion, can be drawn conclusion on the results of research as follows. There is a positive and significant relationship between language attitudes with writing narrative competence . There is a positive and significant relationship between knowledge of Indonesian spelling (EBI) with writing narrative competence . There is a positive and significant relationship between language attitudes and knowledge of Indonesian spelling (EBI) together with writing narrative competence . Keywords: Writing Narrative Competence, language attitudes, and knowledge of Indonesian spelling (EBI)